Post-translational modifications as a key mechanism for herpes simplex virus type I evasion of host innate immunity - Zhang, Yongxing; Xie, Junlei; Feng, Ying; Qadeer, Abdul; Li, Shanni; Deng, Xu; Zhu, Lipeng; Kong, Bo; Xia, Zanxian (Frontiers in Microbiology, 2025)
Herpes simplex virus type 1 (HSV-1) is a DNA virus that infects humans and establishes long-term latency within the host. Throughout its prolonged interaction with the host, HSV-1 evades the innate immune system by encoding its own proteins. Post-translational modifications (PTMs) of these proteins play crucial roles in their function, activity, and interactions with other factors by modifying specific amino acids, thereby enabling a diverse range of protein functions. This review explores the mechanisms and roles of PTMs in HSV-1-encoded proteins, such as phosphorylation, ubiquitination, deamidation, and SUMOylation, during HSV-1 infection and latency. These modifications are essential for suppressing host innate immunity, facilitating viral replication, and elucidating the crosstalk among various post-translational modifications.